Theory of the energy fluctuation of multicomponent alloys. (15th March 2019) - Pei, Zongrui
Abstract: Structural models are usually employed to calculate the physical properties of random alloys. The "Special Quasirandom Structures" (SQS) method was proposed to maximize the randomness of systems with given sizes in 1990. However, hitherto there is no theory to guide the finding of such system sizes with appropriately small energy fluctuations as input for the SQS method. To this end, we propose an effective theory to treat the fluctuations of energies for random multicomponent alloys. The theory is validated by accurate Wang-Landau Monte Carlo sampling in the cases of body-centered cubic FeCo and face-centered cubic NiCoCr alloys. Graphical Abstract: